Enzymes in Oil Processing : Recent Developments and Applications - Showkat, Ahmad Bhawani (Elsevier Inc., 2024)
Enzymes in Oil Processing: Recent Developments and Applications provides solid, quantitative descriptions and reliable guidelines surrounding the development of enzyme technology for oil processing. This book provides comprehensive understanding of topics such as enzymatic degumming, enzymatic interesterification and enzymatic biodiesel production, focusing on the different enzyme assisted extraction methods used in oil in various sources such as soybean, canola, corn, olive, etc. The book also highlights the most exciting enzymatic transesterification of cooking oil and bioremediation of cooking oil waste by lipases. This book will be of interest to researchers working in the fields of enzymes, oil processing, applied science and bio-wastes.